Hugh MacDiarmid’s Influence on the Scottish Literary Revival - Szamosi, Gertrúd (FOCUS: Papers in English Literary and Cultural Studies, 2020)
The interwar period of national revival produced a great variety of literary, critical, social, political and philosophical writings that have commonly been referred to as “The Scottish Renaissance.” The term was first used in its new sense in the first issue of The Scottish Chapbook of August 1922, published by Christopher Murray Grieve, better known by his pen name, Hugh MacDiarmid. In comparison with earlier attempts to renew Scottish culture, the single most distinctive feature of this movement was the belief that “there could be no regeneration of the nation’s artistic culture which did not also involve the regeneration of the social, economic and political life of the nation”(McCulloch xiii).